Postoperative Pain Management: Neurosurgical Vs General Surgical Approaches - Muhammad Azam, Varda Balouch, Zahid Saeed, Samina Karim, Abid Hussain, Muhammad Idrees Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To compare postoperative pain levels, analgesic use, and recovery outcomes between neurosurgical and general surgical patients, with a focus on optimizing pain control while minimizing opioid reliance. Methods: A total of 73 patients undergoing either neurosurgical or general surgical procedures were enrolled between August 2022 and July 2023 in Neurosurgery and General Surgery Units, Saidu Group of Teaching Hospitals, Swat. Pain was assessed using the Visual Analog Scale (VAS) at 6 and 24 hours postoperatively. Data on analgesic use, time to ambulation, patient satisfaction, and complications were collected. Group comparisons were made using appropriate statistical tests, with significance set at p < 0.05. Results: Neurosurgical patients reported significantly higher pain scores at both 6 and 24 hours postoperatively and required more opioid analgesics. Patient-controlled analgesia was more frequently used in this group. General surgical patients, who received more non-opioid analgesics and regional blocks, demonstrated faster ambulation and shorter hospital stays. Despite these differences, overall satisfaction with pain management was comparable between the groups. Conclusion: Pain experiences and management needs differ significantly between neurosurgical and general surgical patients. Tailoring postoperative analgesia through multidisciplinary, procedure-specific protocols can improve outcomes and reduce opioid dependency. Keywords: Postoperative pain, neurosurgery, general surgery, opioid use, regional anesthesia, multimodal analgesia, pain recovery